Implementasi Pendidikan Inklusi dalam Setting Sekolah Menengah Atas di Kota Mataram Provinsi Nusa Tenggara Barat - Gusti, Notonagoro Sabdo (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to describe the implementation of inclusive education in high school settings in the city of Mataram. This research used a qualitative approach with a case study method carried out to see and observe a program, activity, event, or group of individuals at SMAN 6 Mataram. Data collection techniques used interviews and observation.Â Data analysis technique used three stages; data reduction, data exposure, and conclusion drawing. The research results showed that the inclusive education at SMAN 6 Mataram was well implemented because the school had previously carried out socialization to all teachers and parents. In addition, the school provided access for all students with disabilities with individual or additional learning, curriculum modifications for all disabled people, learning facilities, socialization of learning braille books for teachers and assisting students with disabilities in exams. The obstacles experienced were the lack of direct support from the government, professionals, and learning problems such as mathematics, arts and culture, physical education, and crafts.